2003
DOI: 10.1007/s00384-002-0396-5
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin improves symptoms of acquired uncomplicated diverticular disease of the colon

Abstract: Cyclic administration of rifaximin is effective in obtaining symptom relief in uncomplicated diverticular disease of the colon. The incidence of episodes of diverticulitis in the group treated with rifaximin was lower than that in the group treated with glucomannan alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(123 citation statements)
references
References 33 publications
1
113
0
9
Order By: Relevance
“…65 Multiple studies have shown that rifaximin can effectively improve symptoms and maintain periods of remission in patients with uncomplicated diverticular disease, while also being well tolerated. [66][67][68][69][70] …”
mentioning
confidence: 99%
“…65 Multiple studies have shown that rifaximin can effectively improve symptoms and maintain periods of remission in patients with uncomplicated diverticular disease, while also being well tolerated. [66][67][68][69][70] …”
mentioning
confidence: 99%
“…RIFax was effective in both acute and chronic hepatic encephalopathy (Loguercio et al, 2003;Mas et al, 2003). Several recent clinical trails have recommended the use of RIFax for prevention of the main complications in patients with diverticular disease (Latella et al, 2003;Pistoia et al, 2004;Papi et al, 2005). In patients with gasrelated symptoms, the colonic production of H 2 is increased, and RIFax significantly reduces this production and the excessive number of flatus episodes (Di Stefano et al, 2000).…”
mentioning
confidence: 99%
“…The RCT found that, at 1 year, dietary fiber supplementation plus rifaximin significantly improved global symptom score compared with dietary fiber supplementation alone [Latella et al 2003]. …”
Section: Rifaximin Plus Dietary Fiber Supplementation Versus Dietary mentioning
confidence: 99%